1975
DOI: 10.1139/b75-162
|View full text |Cite
|
Sign up to set email alerts
|

Water relations parameters on single leaves obtained in a pressure bomb and some ecological interpretations

Abstract: The physical implications of the various parameters obtained from a pressure-bomb study are explored and related to their possible ecological significance. Our analysis suggests that the original bulk osmotic pressure, the bulk osmotic pressure at incipient plasmolysis, and cell wall elasticity are closely associated with the extent to which a leaf can osmoregulate or conserve water within a certain range of water potential change in the environment and might therefore have certain adaptive value. The pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
120
1
3

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(138 citation statements)
references
References 7 publications
10
120
1
3
Order By: Relevance
“…It was observed that at any given water content, the flag leaf had a lower i than the lower leaves. This property offlag leaves can also be ascribed to the different cellular structure of the leaves since the cells with thicker cell walls, as postulated for the flag leaf, are expected to show a sharper decline in their 4P in response to a given change in water content than the cells with less rigid cell walls, as in the other leaves (6,16,28). Therefore, a flag leaf will reach lower values of water potential faster than the other leaves as the sun rises, and it would maintain this for the whole day although the water content would not decrease much.…”
Section: Discussionmentioning
confidence: 94%
“…It was observed that at any given water content, the flag leaf had a lower i than the lower leaves. This property offlag leaves can also be ascribed to the different cellular structure of the leaves since the cells with thicker cell walls, as postulated for the flag leaf, are expected to show a sharper decline in their 4P in response to a given change in water content than the cells with less rigid cell walls, as in the other leaves (6,16,28). Therefore, a flag leaf will reach lower values of water potential faster than the other leaves as the sun rises, and it would maintain this for the whole day although the water content would not decrease much.…”
Section: Discussionmentioning
confidence: 94%
“…The results suggest that elevated CO2 increases the elasticity of tissues, thereby facilitating the maintenance of turgor over a greater change in water content and hence, water potential (Cheung, Tyree & Dainty, 1975), The greater elasticity of tissues might have facilitated grow^th of sugar maple under elevated CO3, as shown by the 10-fold increase in leaf area (Tschaplinski et al, 1995). A similar increase in elasticity of three herbaceous species, including Lotus corniculatus, S. minor, and P. media W'ith plants grown in elevated CO.^ was reported by .…”
Section: Drought and Co^ Effects On Osmotic Potential Of Leavesmentioning
confidence: 99%
“…For example, drought reduced the water saturation deficit of sugar maple (a drought avoidance response), whereas drought increased the water saturation deficit in sweetgum (a drought tolerance response). The increase in e^^^ of sycamore under drought is a drought avoidance response, where the decrease in tissue elasticity results in a greater decline in water potential and turgor pressure per unit water loss (Cheung et al, 1975).…”
Section: Drought and Co^ Effects On Osmotic Potential Of Leavesmentioning
confidence: 99%
“…From each pressure-volume curve, the following three parameters were calculated: the osmotic potential at saturation (Ψπfull), the osmotic potential at the turgor loss point (Ψπ0) and the modulus of elasticity (Emax - Cheung et al 1975, Jones & Turner 1980, Tyree & Jarvis 1982, Bowman & Roberts 1985. Twelve randomly chosen plants per treatment were analyzed (1 PV curve per plant; two plants per block).…”
Section: Pressure-volume Curves and Water Parameter Analysismentioning
confidence: 99%